Exemplary Youth Leadership Series: Challenge the Process - Megan Stein (EDIS)
This publication series is designed to outline strategies and experiences to expose and engage youth with leadership concepts. In this publication, students will try on aspects of the third practice of exemplary leaders: challenge the process (Kouzes & Posner, 2018). Two low-cost, quick activities are included for implementation with youth and adults working with youth. These activities are best suited for students ages 10–18. However, modifications are included for each of the activities to allow for different group sizes, ages, and abilities of the youth involved.